The effect of countermovement on force production capacity depends on extension velocity: A study of alpine skiers and sprinters - Cross, M. R.; Riviére, J. R.; Van Hooren, B.; Coulmy, N.; Jiménez-Reyes, P.; Morin, J.-B.; Samozino, P. (Journal of Sports Sciences, 2021)
In jumping, countermovement increases net propulsive force and improves performance. We aimed to test whether this countermovement effect is velocity specific and examine the degree to which this varies between athletes, sports or performance levels. Force-velocity profiles were compiled in high-level skiers (N= 23) and sprinters (N= 30), with their performance represented in their overall world ranking and season-best 100 m time, respectively. Different ratios between force-velocity variables were computed from squat and countermovement jumps (smaller = less effect): jump height (CR(h)), maximum power (CR(p)), force (CR(F)), and velocity (CR(v)). Countermovement effect differed per velocity (inverse relationship between CRF and CR(v), r(s) = -0.74, p< .001), and variation force-velocity profiles with countermovement. Skiers exhibited smaller CRF (r(rb) = -0.675, p< .001), sprinters smaller CR(v) (r(rb) = 0.426, p= .008), and "moderate" velocity conditions did not differentiate groups (CR(p) or CR(h), p> .05). 33% of the variance in skiers` performance level was explained by greater maximum force and a lower CR(F) (i.e., high explosiveness at low-velocities without countermovement), without an association for sprinters. Countermovement effect appears specific to movement velocity, sport and athlete level. Consequently, we advise sports-specific assessment, and potentially training to reduce the countermovement effect per the relevant velocity.